Catalytic Friedel‐Crafts Reactions on Saturated Heterocycles and Small Rings for sp3‐sp2 Coupling of Medicinally Relevant Fragments. Issue 31 (12th June 2019) - Croft, Rosemary A.; Dubois, Maryne A. J.; Boddy, Alexander J.; Denis, Camille; Lazaridou, Anna; Voisin‐Chiret, Anne Sophie; Bureau, Ronan; Choi, Chulho; Mousseau, James J.; Bull, James A.
Abstract : gem ‐Diarylheterocycles display a wide range of biological activity. Here we present a systematic study into the formation of 4‐ to 6‐membered O‐ and N‐heterocycles and cyclobutanes bearing the diaryl motif through a catalytic Friedel–Crafts reaction from the corresponding benzylic alcohols. 3, 3‐Diaryltetrahydrofurans, 4, 4‐diaryltetrahydropyrans, 3, 3‐diarylpyrrolidines, 4, 4‐diaryl‐piperidines, as well as diarylcyclobutanes are examined, with results for 3, 3‐diaryloxetanes and 3, 3‐diarylazetidines presented for comparison. Three catalytic systems are investigated for each substrate [Ca(II), Li(I) and Fe(III)], across preinstalled aromatic groups of differing electronic character. In most cases examined, the diaryl product is obtained directly from the alcohol with good yields using the most appropriate catalyst system. In the absence of a nucleophile, the olefins from the 5‐ and 6‐membered substrates by elimination of water are obtained under the same reaction conditions. Abstract : A systematic comparison of Lewis acid catalysts [Ca(II), Li(I) and Fe(III)] is presented for catalytic Friedel–Crafts reactions using alcohols on 4‐, 5‐, and 6‐membered oxygen and nitrogen heterocycles and cyclobutanes, forming gem ‐diaryl quaternary centers.